Electrochemical Approach to Measure Physiological Fluid Flow Rates - Sarathy, Srivats; Nino, Marco A.; Ghanim, Abdulsattar H.; Rajagopal, Srinivasan; Mubeen, Syed; Raghavan, M. L. (Frontiers in Chemistry, 2021)
In vivo measurement of the flow rate of physiological fluids such as blood flow rate in the heart is important in critically ill patients and for those undergoing surgical procedures. The reliability of these measurements is therefore quite important. However, current methods in practice for the measurement of flow rates of physiological fluids suffer from poor repeatability and reliability. Here, we assessed the feasibility of a flow rate measurement method that leverages time transient electrochemical behavior of a tracer that is injected directly into a medium [That electrochemical signal caused due to the tracer injectate will be diluted by the continued flow of the medium and the time response of the current – the electrodilution curve – will depend on the flow rate of the medium]. In an experimental flow loop apparatus equipped with an electrochemical cell, we used the AC voltammetry technique and tested the feasibility of electrodilution-based measurement of flow rate using two mediums – pure water and anticoagulated blood – with 0.9 wt.% saline as the injectate. The electrodilution curve was quantified using three metrics – change in current amplitude, total time, and change in the total charge for a range of AC voltammetry settings (peak voltages and frequencies). All three metrics showed an inverse relationship with the flow rate of water and blood with the strongest negative correlation obtained for change in current amplitude. The findings are a proof-of-concept for the electrodilution method of flow rate measurement and offer the potential for physiological fluid flow rate measurement in vivo.